The Effects of Yoga in Patients Suffering from Subjective Tinnitus - Köksoy, Sümbüle; Eti, Can Mehmet; Karataş, Meltem; Vayisoglu, Yusuf (International Archives of Otorhinolaryngology, 2018)
Introduction Tinnitus is a perception of sound in the absence of an external source and it is a distressing issue. Yoga is a system of mind-body practices with the goal of uniting the body, mind and soul. It has been shown to reduce anxiety and stress, as well as improving the quality of life.Objective The aim of this study is to investigate the effects of yoga in patients suffering from chronic subjective tinnitus.Methods Twelve subjects previously diagnosed with chronic subjective tinnitus were selected for the study. The patients were asked to attend to yoga classes once a week and to practice yoga at home using a worksheet for 3 months. Each yoga class consisted of body exercises (asana), breathing (pranayama) and meditation (shavasana and yoga nidra). Tinnitus scores before and after the yoga classes were compared using the Wilcoxon test.Results Among the 12 patients, there were 4 men and 8 women and their mean age was 52.5 years. The median duration of tinnitus among the group was 5.4 years. There were statistically significant differences in the stress (p = 0.01), handicap (p = 0.004) and severity (p = 0.007) questionnaires scores.Conclusion This study indicated that yoga practices may reduce life stress and symptoms of subjective tinnitus.
Keywords: complementary and alternative medicine; tinnitus; yoga; complementary therapies